WHY HAVE HEPATITIS B BIRTH DOSE RATES DECREASED IN JOHNSON COUNTY? A PRELIMINARY QUALITY IMPROVEMENT PROJECT - Schroeder, Kealan (My University, 2013)
The World Health Organization recommended that the Hepatitis B vaccination be added to the universal vaccination programs in all countries in 1991. Incidence of acute Hepatitis B in the United States decreased 75% from 1991 – 2004 (Mast et al., 2005). This success not only is due to the WHO, but also due to the United States government supporting Hepatitis B perinatal programs. The United States Advisory Committee on Immunization Practices (ACIP) which recommends all infants are given the Hepatitis B birth dose (Hepatitis B infant vaccine) before being discharged from the hospital. The Vaccines for Children Program from Centers for Disease Control and Prevention (CDC) offers childhood vaccinations at no charge for qualifying individuals. This includes uninsured, underinsured, Medicaid-eligible, Native American, and Native Alaskan children (CDC, Vaccines for Children Program, 2012). Despite efforts made by federal, state, and local governments, between the years 2005 and 2010, Hepatitis B birth dose rates for infants in Johnson County, Kansas have drastically declined – 92.2% coverage in 2005 to 69.9% coverage in 2010. The purpose of this study is to identify problems that act as barriers to receiving the birth dose and to develop Quality Improvement measures to eliminate them. Thoughts were organized and an internal source survey (JCDHE employees) was conducted to put the results into Quality Improvement tools. The outcome of this study will be useful for answering the question of why the Hepatitis B birth dose rate has dropped in Johnson County, Kansas and suggestions to increase the rate of vaccination.
Keywords: Hepatitis B; Public Health; Johnson County Kansas; Public Health (0573)